MEMBANGUN BUDAYA LITERASI BAGI GURU DAN KEPALA SEKOLAH PROFESIONAL PADA ERA REVOLUSI INDUSTRI 4.0 - Ririn Oktarina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This article describes how to build a literacy culture for teachers and principals to be more professional in working in the current era of industrial revolution 4.0. Literacy culture is very necessary to face the era of industrial revolution 4.0 which is characterized by increasing interaction between humans, machines and other resources through information and communication technology. In the era of revolution 4.0, the education community, especially teachers and school principals, were required to master